E-Bike Conversion Kit - Muhammad Akmal, Muhammad Ammar Haziq; Sayfulidham, Shakir Aiman; Chandran, Darshan; Mohamed Nor, Mohd Hadri (Multidisciplinary Applied Research and Innovation, 2025)
The E-Bike Conversion Kit project was chosen in response to the increasing need for sustainable, affordable, and practical transportation solutions among university students. Many students living on campus face challenges such as long walking distances between classes, limited access to affordable personal vehicles, and reliance on environmentally detrimental transportation options. These issues highlight a gap in accessible and eco-friendly transportation solutions tailored specifically for the university demographic. The idea for this project emerged from research and observations of student lifestyles. Studies have shown that bicycles remain a popular choice for university students due to their affordability and health benefits. However, traditional bicycles can be impractical for students dealing with steep terrains, tight schedules, or physical limitations. Meanwhile, electric bicycles (e-bikes) provide a viable alternative but are often prohibitively expensive for students. This creates an opportunity to develop a cost-effective solution that bridges the gap between affordability and functionality. The project incorporates a secure fingerprint recognition system to address concerns about bike theft, which is a common issue on campuses. By enhancing the security of e-bikes, the project ensures peace of mind for students, allowing them to focus on their studies without worrying about the safety of their transportation. Additionally, the modular design of the conversion kit was inspired by the growing trend toward customizable and user-friendly technology. This feature allows students to adapt their bikes to suit individual needs and preferences, making the solution versatile and appealing to a broader audience. Overall, this project underscores the commitment to creating an environmentally sustainable future while addressing the specific needs of university students. By reducing reliance on traditional motor vehicles, it supports the global shift toward greener transportation alternatives while promoting the well-being and convenience of students.